LINGUACULTURAL AND COGNITIVE ASPECTS OF ETHONYMS - Nurtayeva Zebuniso Murodali qizi (TADQIQOTLAR.UZ, 2024)
Abstract. This article explores the linguacultural aspects of ethonyms, highlighting their significance in reflecting and shaping cultural identities and social dynamics. Ethonyms, or names given to ethnic groups, are more than mere labels; they carry deep cultural, social, and historical meanings. The discussion covers how ethonyms serve as markers of identity, reflect stereotypes and connotations, and are influenced by language policies and official recognition. The distinction between endonyms and exonyms underscores the power dynamics in naming practices. The article also delves into the historical and social contexts of ethonyms, their role in national identity, and their reflection of linguistic diversity.